Social media and migrants’ perceptions: Portugal as a potential host country for Brazilian workers - Nunes, Flávio (Human Geography Journal, 2022)
Social media use is increasingly affecting the various stages preceding the decision to emigrate, including the selection of final destination. Future migrants meaningfully use ICT to connect with those workers who are already living abroad, as a result more accurate perceptions of host societies are emerging through peers’ experiences. This study evaluates the specific role played by YouTube in the way Brazilians are creating their mental images of Portugal. A sample of 135 YouTube videos were analyzed, in which Brazilian emigrants share their testimonies of adaptation to the Portuguese reality. The conclusions point out to a mismatch between the low skills’ jobs, locally available in the Portuguese labor market, and the higher qualification profile of many Brazilian workers who moved to Portugal. If expectations must be reduced in terms of economic prosperity, there is a consensus regarding a higher quality of life, in a broader sense, experienced by Brazilian migrants after their decision to live and work in Portugal. Based on the specific results of this study it possible to highlight some consensus among the testimonies analyzed which, for that reason, assume a non-negligible importance in the perceptions about Portugal that are being structured by potential Brazilian migrants, also due to the high number of views and shares these videos receive. These points of consensus deserve reflection by those who study migrations and define policy guidelines on migratory processes, especially in a country whose government has assumed the importance of immigration as a way to mitigate the effects of the alarming demographic ageing of the Portuguese society. Among these points of consensus are the warnings about the initial difficulties of integration into the labor market and the need to accept job offers that do not match the qualification profiles and professional skills developed in Brazil. There is also a warning about the need to reduce expectations regarding an eventual ambition of a substantial improvement of the financial conditions of these migrants. Although such difficulties do not condition an evident progress in terms of comfort and quality of life, which ends up providing a general satisfaction among Brazilians who decided to choose Portugal as their emigration destination.